Service Life Design of Deck Closure Joints in ABC Bridges: Guidelines and Practical Implementation - Jaberi Jahromi, Azadeh; Valikhani, Alireza; Mantawy, Islam M.; Azizinamini, Atorod (Frontiers in Built Environment, 2020)
Closure joints are commonly used in bridge deck to connect two adjacent prefabricated elements in accelerated bridge construction. The current practice of closure joints utilizes the use of different materials such as normal strength concrete and ultra-high performance concrete with the use of different reinforcement details such as straight bars, hooked bars, and headed bars. The design of closure joint to meet strength limit state is quite simple, however, the design for service life for these joints is quite challenging. Framework for service life design of closure joints in bridges, built using accelerated bridge construction techniques, is developed in this paper. This framework includes several steps: 1) identification of project requirements especially those influences the service life of closure joints; 2) identification and selection of feasible closure joint types suitable for the project requirements; 3) identification of factors which influence the service life of closure joints along with mode of failures and consequences; 4) identification of suitable approaches or strategies for mitigating failure modes or assessing the risk of damage; 5) modification of closure joint detail using mitigation strategies which may result in the development of several alternatives and options for each closure joint type; 6) estimation and comparison of service life for each modified alternative using finite or target service life approach; and 7) conducting life-cycle cost analysis for each modified alternative along with the selection of the optimum closure joint details to meet both strength and service life demand. This framework is used in practical design implementation example for 1400-ft long bridge in Boston, Massachusetts, US. Several closure joints details were studied under this research such as the use of normal strength concrete with straight bars, 180-degree hooked bars, 90-degree hooked bars, and headed bars along with the use of ultra-high performance concrete with straight bars. This paper summarizes the outcome of the design for service life of those closure joints comparatively.